Development and implementation of GPS for location tracking / Ahmad Ashraff Ariffin - Ariffin, Ahmad Ashraff (2011)
The use of satellite application for modern transport navigation is well established worldwide. Travelling through air and sea rely heavily on this technique of obtaining accurate and reliable positioning information. In recent years however, satellite navigation has started to expand into other areas such as recreation and emergency response. There is no doubt that this method of acquiring position is here to stay, and will continue to adopt into new applications. With today's stand alone global position system receivers, you are able to pinpoint your own position. But, what's more useful about stand alone GPS receivers it can measure a distance by know two points in the earth. Therefore this project is an attempt to design and implement Global Positioning System for hiking, climbing and boating inexpensive. The function of GPS is to locate the position of user and send a right direction from satellites. The signals from satellite will be shadowed by buildings, terrain, rain and also manmade obstacles that effects the accuracy of GPS range measurement. The hardware that was used is PIC18F4520 which integrated with GPS receiver typed FV-M8. This GPS will give the coordinates of latitude and longitude as well as the bearing angles between two positions. The algorithm of calculating the distance between these two positions also was developed by using PIC C Compiler. This algorithm has the ability of extract the data from GPS receiver and communicate via RS232 to test the interaction from GPS receiver. The microcontroller will be used to parse the NMEA data sentences and calculate the algorithm. Finally, the output will be displayed to LCD. After a several experiments that have been conducted in different location, view and weather, the results give an average of 10% slightly different compare with theoretical.